Neue ternäre Vanadyl(IV) Komplexe mit ADP und AMP - Ferrer, Evelina Gloria (1995)
Four new ternary V02+ complexes, [VO HADP-dipy], 6H20, [VO HADP-ophen], 6H20, [VO AMP-dipy], 6H20 and [VO AMPophen]. 6H20 (diny: a.a'dipyridyl; ophen: o-phenanthroline) were prepared and characterized by chemical analyses, electronic and vibrational spectra. Their bonding peculiarities are briefly discussed.